Analisis Kepuasan Masyarakat Dalam Pelayanan Publik Pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wajo - Iwan Mamminanga; Yusran Yusuf; Sofyan Marzuki (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study was conducted at the Population and Civil Registration Office of Wajo Regency. The research aims to assess public satisfaction with the public services provided by the Population and Civil Registration Office of Wajo Regency using a descriptive method with a qualitative approach. Public satisfaction, based on indicators such as service procedures, service requirements, service speed, and service fairness, has not been fully met. This conclusion was derived from observations, document analysis, and interviews with informants, including the Head of the Population and Civil Registration Office of Wajo Regency, the Secretary of the Population and Civil Registration Office of Wajo Regency, and key community members who use the services of the office. Recommendations suggest that the Population and Civil Registration Office of Wajo Regency should maintain and further optimize all indicators of satisfaction to enhance public service quality.